Development of 3D microscope for surface texture measurement - Sng, Bryan Zhe Yuan (Nanyang Technological University, 2022)
As technology advances, surface inspection has started playing significant roles in various industries. Some industries require the visualization of whole surfaces, regardless of roughness. Irregularities and surface features are equally important aspects of surface profiles. Therefore, these features need to be easily visualized and identified when scanning a surface.